Strategic management and leadership: a bibliometric analysis - Shazleen Abdul Latip; Faerozh Madli; Azaze Azizi Abdul Adis; Haslinda Hassan (Penerbit UMS, 2022)
Organizations today require excellent strategic management and skilled leadership to achieve their aims and objectives. Strategic management and leadership are two distinct concepts with distinct meanings that appear to act in various ways. The goal of this paper’s research is to conduct a bibliometric evaluation and a visualization analysis of the strategic management and leadership relationship. This paper’s goal is to scientifically document the intellectual structure, volume, and knowledge development directions. A Scopus Database and VOS Viewer software was applied as method to collect data and analysis the data. From the database, excel and VOS viewer, the total 342 of articles related with the topic the result of the paper was found and the relevant article can be used is 58 articles. As a result, the volume of articles on strategic management and leadership published in the span of the year 2012 until the year 2021 remains unstable as it decreases and increase as the time passes. The most influential journals, authors, and publications in the researched topic are identified through bibliometric analysis. This study reveals that by combining the most important aspects of strategic management and leadership into a single concept, it can lead to new research directions in business, management and accounting filed.